PLIN5 contributes to lipophagy of hepatic stellate cells induced by inorganic arsenic - Haomiao Li; Xuri Xie; Tianming Qiu; Jingyuan Zhang; Jie Bai; Guang Yang; Ningning Wang; Xiaofeng Yao; Xiance Sun (Ecotoxicology and Environmental Safety)
Arsenic exposure triggers the activation of hepatic stellate cells (HSCs), resulting in liver fibrosis (LF). A significant decrease in lipid droplets marks the activation of HSCs. However, the exact underlying molecular mechanism remains elusive. Lipophagy, a specialized form of selective autophagy, is crucial for the degradation of lipid droplets to maintain intracellular lipid metabolism homeostasis. In this study, arsenic treatment induced lipophagy, as evidenced by the co-localization of LC3 with lipid droplets. Remarkably, arsenic exposure increased the expression levels of Perilipin 5 (PLIN5), a lipid droplet-associated protein, both at the mRNA and protein levels. Moreover, silencing PLIN5 influenced arsenic-induced lipolysis. Consequently, the results of this study indicate that PLIN5 serves as a substrate protein involved in arsenic-induced lipophagy. This research offers a novel perspective on the mechanisms of arsenic-induced HSCs activation and liver lipid metabolism, potentially guiding new strategies for the prevention and treatment of arsenic-related liver diseases.